Neutrosophic modules over modules - Ali Yahya Hummdi; Amr Elrawy; Ayat A. Temraz (AIMS Mathematics)
A module represents a fundamental and complicated algebraic structure associated with a particular binary operation in algebraic theory. This paper introduces a new class of neutrosophic sub-module and neutrosophic R-sub-module. We extend the basic definitions in this area for the first time. Various properties of a neutrosophic R-sub-module are studied in different classes of rings. Moreover, various definitions of direct product and homomorphism of neutrosophic R-sub-modules are discussed, and results are provided.